Prediction of Deleterious Non-Synonymous Single Nucleotide Polymorphisms (Nssnps) of Human TLR7 Gene - Gaaib, Jawdat N. (Iraqi Journal of Science, 2022)
Toll-like receptors (TLRs) play a key role in innate immune response activation against viruses. TLR7, one of the TLRs family, is potentially important in controlling viral infection and the production of vaccines against the virus. The wide spectrum of discrepancy in response to antiviral drugs among different populations which is emerged by some pandemics like COVID-19 might be due to their different TLR7 single nucleotide polymorphisms (SNPs). The present study aimed to investigate the consequences of 401 non-synonymous missense SNPs (nsSNPs) within TLR7 on its protein structure, stability, and function by using specific bioinformatics tools. Seven bioinformatics tools were used to investigate 401 TLR7 nsSNPs from the dbSNP database. The results showed that the six variations, rs1171508003 (R262H), rs35160120 (F580S), rs968155471 (H587Q), rs202028806 (Y871D), rs1331496205 (W933S), and rs181600414 (R1004W), were found to be extremely deleterious by all of the employed bioinformatics tools. All six variations showed an impact on the protein’s structure, function, and stability. Among them, Y871D (rs202028806) and R1004W (rs181600414) were revealed as the most damaging nsSNPs. This study suggested that the predicted six damaging variants of TLR7 could indirectly or directly destabilize the structure of protein and deviate its function to some extent.